New records of griffin’s leaf-nosed bat (Hipposideros griffini Thong et al. 2012) from Vietnam - Thong, Vu Dinh (Academia Journal of Biology, 2012)
Griffin’s Leaf-nosed bat (Hipposideros griffini) is one of the largest species of the family Hipposiderodae. In the field, it is recognisable from other hipposiderid species of Vietnam by body size, noseleaf structure, and echolocation frequency. Prior to this study, Hipposideros griffini was only known from two national parks (Cat Ba and Chu Mom Ray) in Vietnam. This paper provides new data recorded from Cat Tien national park, Southern Vietnam, indicating a more extensive distribution of Hipposideros griffini. Results from previous and current studies indicate that Griffin’s Leaf-nosed bat inhabits in various habitats ranging from flat/lowlands to offshore islands, mountainous and karst areas.